Feeding level is associated with altered liver transcriptome and follicle selection in hen. Issue 5 (27th January 2022) - Stephens, Claire S; Hill-Ricciuti, Alexandra; Francoeur, Laurie; Johnson, Patricia A
Abstract: Genetic selection for particular traits in domestic animals may have altered the optimal feedback regulation among systems regulating appetite, growth, and reproduction. Broiler breeder chickens have been selected for fast and efficient growth and, unless feed restricted, consume excessively resulting in poor reproductive efficiency. We examined the effect of dietary treatment in full-fed and restricted-fed broiler breeder hens on ovarian responses, liver morphology, and transcriptome associated with reproductive function. Although full-fed broiler breeder hens had lower egg production ( P  < 0.01), the total number of ovarian follicles >8 mm ( P  < 0.01), 6–8 mm ( P  < 0.03), and 3–5 mm ( P  < 0.04) were greater in full-fed hens compared to restricted-fed hens. There was a large amount of lipid accumulation in the liver of full-fed hens and differential gene analysis yielded 120 genes that were differentially expressed >2-fold in response to feeding level ( P  < 0.01; false discovery rate < 0.05). Elevated T3 may indicate that general metabolism was affected by diet and GHR ( P  < 0.01) and insulin like growth factor 1 ( IGF1 ) ( P  < 0.04) mRNA expression were both greater in the liver of full-fed hens as compared to restricted-fed hens. It is likely that selection for increased growth, associated with enhanced activity of the IGF1 system, has altered nutritional coupling of feed intake to follicle development. Abstract : Feeding level affects the liver and ovary of the hen. Graphical Abstract: